Electromagnetic shielding effectiveness of fiber-reinforced composites: a preliminary study - Munalli, Daniela; Chronopoulos, Dimitrios; Greedy, Steve (2018)
The use of Low power Radio Frequency (RF) based techniques as Non Destructive Testing (NDT) methods offers a potential solution for detecting defects and anomalies occurring in the structural integrity of composite based structures in real time, enabling better scheduling of servicing, repair and maintenance and eventual decommissioning of aircraft structures. Therefore preliminary results regarding the measurements of electromagnetic shielding effectiveness (SE) of diverse conductive fiber-reinforced composites will be reported. This investigation has been carried out with a coaxial transmission line testing chamber according to ASTM 4935 in the Radio spectrum, by means of comparisons between electromagnetic waves propagation in composites and traditional conductive materials, and through changes in electromagnetic shielding performances, based on the structural characteristics of the composite material.